SISTEM ADAT PERNIKAHAN DALAM PANTUN ADAT MINANGKABAU: KAJIAN SEMIOTIK RIFFATERRE - Wulandari, Yosi; Pradipta, Diksi (Jurnal Tradisi Lisan Nusantara, 2024)
Minangkabau is one of areas Minangkabau is one of the areas in West Sumatra that still adheres to the culture of chanting to convey messages on certain occasions, especially at weddings. This study aims to describe the significance of the traditional marriage system in Minangkabau tra-ditional rhymes. This type of research is descriptive qualitative using the method of observing and note-taking techniques. Data analysis techniques in this study were carried out by means of qualita-tive descriptive analysis with semiotic readings according to Michael Riffaterre. The results of the study show that there is a customary marriage system in Minangkabau traditional rhymes related to the description of marriage customs, tests when they have lived a household life, the course of the wedding party, the nature of husband and wife and the provisions for dividing assets when divorced. In addition, the Minangkabau area has a series of traditional ceremonies that are unique or different from other regions. This research is expected to provide benefits as a vehicle to add insight regarding the customary system of marriage in Minangkabau for the community, parents and students. In ad-dition, this research is expected to be used as a reference for further research.